An approach to the motifs of love and violence in the hellinistic world of Xenophon's Ephesiacs - Álvarez Espinoza, Nazira (2023)
This article presents an approximation to violence as a social micro-space in the novel the Ephesiacs by Xenophon of Ephesus]. Romance and adventure novels are born in an urban geographical setting. These stories have sudden changes of scenery and geography with internal and external spaces. In the internal space, appear the themes and motifs that allow the development of the argument [the themes and motifs that allow the development of the argument appear]. In the external space, can see a space in which adventures take place in cities of the Hellenistic world. The micro-space, in the text, is formed through the social space from the relationships established by the protagonists with the people of these places. Precisely, in the micro-space, the motif of love is intertwined with seduction, chastity, fidelity, separation as well as with violence and slavery. The latter constitutes a reason for constant violence for the young protagonists who defend their fidelity and chastity threatened in hostile environments and alien to the Hellenic world.